Theoretical Evolution of PhD Theses on Public Relations in Turkey Between 1980-2020 - Gülsüm Şimşek; Özlem Işık (Selçuk İletişim)
In the context of the chronological development of public relations theory, this research aimed to reveal the theoretical frameworks of the public relations theses studied in Turkey between 1980 and 2020. The study addressed changes and developments in the context of the chronological progress of the public relations theory that developed in America and Europe, and were subjects of theses studied public relations in Turkey. The population of the study, doctoral theses in the field of public relations in Turkey; the sample is the doctoral theses studied in the field of public relations in Turkey and those were acceptable in data collection time. From the 1980s until 2020, the limitation of the study constitutes the titles and summaries of the top public relations dissertation studied in Turkey. In the theoretical part of the study, the chronological development of the theory of rights relations in the process ranging from system theory to dialogic communication was discussed. In the methodology part, the frequency of the theses studying the public relations in Turkey were mentioned and interpreted based on years, subjects, the application areas in public relations, and related disciplines. Analysis revelaed that the number of doctoral theses in the field of public relations in Turkey increased quantitatively in recent years. The most studied topic was political communication (n=36) whereas the least was the protocol administration. Addition to this, no thesis had been studied on system theory, contingency theory, which is one of the first theories of public relations. With the development of the theories in America and Europe, it was determined that theses in Turkey were parallels to those in America and Europe in the chronological order in the doctoral theses, albeit with an average of 15 years delay in Turkey.